객관적인 마취심도 조절하에서 전신마취 및 수술 전⋅후 사시각의 변화 - 김창주(Chang Zoo Kim), 남기엽(Ki Yup Nam), 이승욱(Seung Uk Lee), 이상준(Sang Joon Lee) (Daihan angwa haghoi jabji, 2018)
목적: 사시 수술 전후와 전신마취하 수술 전후 사시각의 변화에 대해 알아보고자 한다. 대상과 방법: 2014년 1월부터 2017년 10월까지 동일 술자에 의해 시행된 간헐성 외사시 수술 환자 20명을 대상으로 하였다. 환자는 먼저 수술 전 외래(preoperative angle of deviation, PreAn)에서 사시각을 측정하였다. 술 중에는 수술 침대에 누운 상태에서 전신마취 후 Bispectral index를 참조하여 충분한 정도의 진정이 되었음을 확인 후(angle of deviation under general anesthesia, PostAn), 근육 수술이 끝난 직후(angle of deviation before waking from general anesthesia after strabismus surgery, OP end) 디지털 카메라로 수직으로 40 cm 높이에서 촬영하였다. 마지막으로 술 후 6개월째 외래(angle of deviation at 6th month after strabismus operation, 6mon) 방문 시 사시각을 확인하였다. 술 중 사시각은 촬영된 사진을 분석하여 측정하였으며 눈벌어짐은 양의 값으로, 눈모음은 음의 값으로 처리하였다. 결과: 대상자는 남자 10명, 여자 10명, 평균 나이는 7.31 ± 3.59세였다. 술 전 사시각(PreAn)은 원거리 기준 30.0 ± 13.87 PD였으며, 전신마취하 측정된 사시각(PostAn)은 26.46 ± 5.39 PD였다. 술 전 사시각과 전신마취 후 사시각(PostAn)의 변화량은 술 전 사시각과 유의한 양의 상관관계(PostAN-PreAn=-7.67×PreAn+19.57 [R2=0.872, p<0.00])를 보였다. 전신마취 전⋅후(PostAn-PreAn) 사시각의 변화량과 근육수술 직후와 6개월 후 사시각의 변화량(6mon–OP end) 사이에는 유의한 양의 상관관계(6mon-OP end=0.317× [PostAn-PreAn]+13.098 [R2=0.334, p=0.01])를 나타내었다. 결론: 전신마취 후 측정된 사시각은 마취 전 측정값과 유의한 양의 상관관계가 있었다. 마취 전후 사시각의 변화 정도에 따라 수술 직후 보인 사시각과 추후 안정된 각 사이의 변화의 정도를 추정해 볼 수 있을 것이다. Purpose: Changes in angular deviation before and after general anesthesia and strabismus surgery were examined. Methods: Twenty patients with intermittent exotropia who were operated on by the same surgeon from January 2014 to October 2017 were included. The basic angle of deviation (preoperative angle of deviation, PreAn) was measured at an outpatient clinic. While lying on a surgical bed under general anesthesia, the bispectral index was referenced, and it was confirmed that there was a sufficient degree of sedation. Photographs were then taken at a height of 40 cm (angle of deviation under general anesthesia, PostAn); while still under general anesthesia, the same procedure was followed immediately after the end of surgery. At 6 months after surgery, the angle of deviation was measured. Results: There were 10 males and 10 females, and the mean age was 7.31 ± 3.59 years. The preoperative angle of deviation was 30.0 ± 13.87 prism diopters (PD) at far fixation; under general anesthesia, 26.46 ± 5.39 PD. There was a significantly positive correlation between the PreAn and angle of deviation under general anesthesia (PostAn - PreAn = -7.67 × PreAn + 19.57; R2 = 0.872; p < 0.00). The angle of deviation changes between pre- and post-anesthesia (PostAn-PreAn) and at the end point of surgery (OP end) and at 6 months after surgery (6mon) also showed a significantly positive correlation (6mon-OP end = 0.317 × [PostAn - PreAn] + 13.098; R2 = 0.334; p = 0.01). Conclusions: There was a significant positive correlation between the measured angle of deviation pre- and post-anesthesia. We could estimate the degree of change between the angle of deviation immediately after surgery and the stable angle according to the degree of deviation before and after general anesthesia. KCI Citation Count: 0